Advancing Policy and Practice in Medicaid Home and Community-Based Services Quality - Caldwell, Joseph; Machledt, David (Frontiers in Rehabilitation Sciences, 2022)
This policy brief highlights recent developments and future directions in the Medicaid Home and Community Based Services (HCBS) quality policy and practice within the US. • Background is provided about the structure of Medicaid HCBS within the US, the changing landscape of payment and service delivery, and implications for HCBS quality measurement and use. • An overview of a HCBS quality framework is provided that was developed with stakeholder input. Frequently used survey tools, existing quality measures, and measure development are discussed. • Actionable recommendations are made, including establishment of stakeholder input mechanisms, enhanced federal guidance on a core set of measures, improved data collection and stratification to address equity, multiple mechanisms to assess quality, and increased federal investment in HCBS quality infrastructure.